Pengaruh Kinerja Keuangan Terhadap Return Saham Pada Perusahaan Yang Tercatat Di Indeks Saham Syariah Indonesia (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Metty Astuti, 2019. Analysis of the Effect of Financial Performance on Stock Returns on Companies Listed in the Sharia Stock Index. Guided by mrs. Isna Yuningsih and mrs. Dhina Mustika Sari.Stock returns can be used to measure company success and as a consideration in buying company shares. This study aims to analyze the Effect of Current Ratio (CR), Return on Equity (ROE), Debt to Equity Ratio (DER), and Price Earning Ratio (PER) to Returns of Shares in companies listed in the Indonesian Syariah Stock Index from 2014 to 2015 The retrun share in this study is cash dividends. The data analysis method used is multiple regression analysis. The data used is secondary data in the form of company annual reports. The results showed that the Current Ratio, Return On Equity, and Price Earning Ratio had a positive and significant effect on stock returns. Increasing the current ratio will increase stock returns, because with a high current ratio the company means having enough cash to pay cash dividends. Likewise with the increase in return on equity, it will increase stock returns, because high return on equity means having enough profit to pay cash dividends. With the increase in the price earnings ratio, it will increase stock returns, because the high price-earnings ratio means having enough profit to pay cash dividends. While Debt to Equity Ratio does not affect stock returns, because the percentage of high and low debt does not affect the company's decision to pay cash dividends.